Anthropological Approach as a Strategy to Increase Interest in Learning Islamic Education - Firmansyah, Eka; Tobroni, Tobroni; Khozin, Khozin (Sekolah Tinggi Ilmu Tarbiyah (STIT) Muhammadiyah Bangil in collaboration with Letiges & Association of Muslim Community in ASEAN (AMCA), 2024)
This research examines how an anthropological approach can increase interest in studying Islamic religious education at the Muhammadiyah University of Palu. This research uses a qualitative approach with a phenomenological type of research. Data analysis in this research uses single data analysis (individual case analysis), with a data analysis model from Miles and Huberman, through three activities that co-occur: data reduction, data presentation, and conclusion drawing/verification. In this research, it was found that the anthropological approach in Islamic Education learning at Muhammadiyah University in Palu includes (1) an approach appropriate to student culture, (2) translating scientific explanations through local cultural symbols, (3) creating students who uphold the values ​​of wisdom, locally through learning Islamic education. Meanwhile, the impacts given to students are (1) providing comfort and increasing students' interest in learning, (2) helping students understand the material explained by their lecturers, and (3) giving birth to generations of Muslims who respect and uphold local wisdom values. , especially giving birth to a generation that does not conflict between Islam and local wisdom who does not think that local wisdom can tarnish the sanctity of Islam. However, he loves both of them, positions them according to their respective portions, and views them as values ​​that support each other.